2016
DOI: 10.1371/journal.pcbi.1005220
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Simulation Service: Bridging the Gap between the Computational Expert and the Biologist

Abstract: We present StochSS: Stochastic Simulation as a Service, an integrated development environment for modeling and simulation of both deterministic and discrete stochastic biochemical systems in up to three dimensions. An easy to use graphical user interface enables researchers to quickly develop and simulate a biological model on a desktop or laptop, which can then be expanded to incorporate increasing levels of complexity. StochSS features state-of-the-art simulation engines. As the demand for computational powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 46 publications
1
63
0
Order By: Relevance
“…Within lattice approaches, variation exists depending on how each molecule is represented and reaction is modeled. In the well-established reaction-diffusion master equation (RDME) models [27][28][29][30][31][32][33], space is discretized into lattice voxels called subvolumes. In each subvolume, point-like molecules are assumed to be dilute and well-mixed.…”
Section: Introductionmentioning
confidence: 99%
“…Within lattice approaches, variation exists depending on how each molecule is represented and reaction is modeled. In the well-established reaction-diffusion master equation (RDME) models [27][28][29][30][31][32][33], space is discretized into lattice voxels called subvolumes. In each subvolume, point-like molecules are assumed to be dilute and well-mixed.…”
Section: Introductionmentioning
confidence: 99%
“…For precise predictions, we suggest to use our method as a starting point for refinement by means of numerically demanding, but asymptotically exact methods. Although there is a lot of development making stochastic analysis tools with state of the art algorithms and fast implementations ( Drawert et al , 2016 ; Fan et al , 2016 ; Somogyi et al , 2015 ) available for a broad community the optimization of stochastic biochemical systems is hardly performed due to its challenging computational effort ( Poovathingal and Gunawan, 2010 ). With this study, we demonstrated that the proposed method is capable of describing biochemical systems containing intrinsic and extrinsic noise and it represents a promising tool suited for optimization and analysis of distributed, stochastic biochemical reaction systems.…”
Section: Discussionmentioning
confidence: 99%
“…Many other research software systems make use of notebooks, and some incorporate special extensions. StochSS [ 87 ], the GenePattern Notebook [ 88 ], the SAGE math system [ 89 ], and the commercial Mathematica software [ 30 ] all utilize notebooks which are specially tailored or feature special extensions for each respective application. However, none of these approaches attempt to solve the problem we address: workflow integration with exchangeable standards.…”
Section: Discussionmentioning
confidence: 99%